Barriers and facilitators to institutional delivery in rural areas of Chitwan district, Nepal: a qualitative study - Rajani Shah; Eva A. Rehfuess; Deepak Paudel; Mahesh K. Maskey; Maria Delius (BMC, 2018)
Abstract Background Giving birth assisted by skilled care in a health facility plays a vital role in preventing maternal deaths. In Nepal, delivery services are free and a cash incentive is provided to women giving birth at a health facility. Nevertheless, about half of women still deliver at home. This study explores socio-cultural and health service-related barriers to and facilitators of institutional delivery. Methods Six village development committees in hill and plain areas were selected in Chitwan district. We conducted a total of 10 focus group discussions and 12 in-depth-interviews with relevant stakeholder groups, including mothers, husbands, mothers-in-law, traditional birth attendants, female community health volunteers, health service providers and district health managers. Data were analyzed inductively using thematic analysis. Results Three main themes played a role in deciding the place of delivery, i.e. socio-cultural norms and values; access to birthing facilities; and perceptions regarding the quality of health services. Factors encouraging an institutional delivery included complications during labour, supportive husbands and mothers-in-law, the availability of an ambulance, having birthing centres nearby, locally sufficient financial incentives and/or material incentives, the 24-h availability of midwives and friendly health service providers. Socio-cultural barriers to institutional deliveries were deeply held beliefs about childbirth being a normal life event, the wish to be cared for by family members, greater freedom of movement at home, a warm environment, the possibility to obtain appropriate "hot" foods, and shyness of young women and their position in the family hierarchy. Accessibility and quality of health services also presented barriers, including lack of road and transportation, insufficient financial incentives, poor infrastructure and equipment at birthing centres and the young age and perceived incompetence of midwives. Conclusion Despite much progress in recent years, this study revealed some important barriers to the utilization of health services. It suggests that a combination of upgrading birthing centres and strengthening the competencies of health personnel while embracing and addressing deeply rooted family values and traditions can improve existing programmes and further increase institutional delivery rates.